Bentuk Surat Kuasa Membebankan Hak Tanggungan Setelah Dikeluarkannya Peraturan Kepala Badan Pertanahan Nasional Nomor 8 Tahun 2012 Tentang Ketentuan Pelaksana Peraturan Pemerintah Nomor 24 Tahun 1997 Tentang Pendaftaran Tanah - Selvyana Putri Pratamikha, Ni Putu (Acta Comitas : Jurnal Hukum Kenotariatan, 2016)
The Power of Attorney of the Encumbrance Rights (SKMHT) is a special power of attorney which includes the power to impose the provision of encumbrance by the encumbrance grantor to the recipient of the encumbrance or other person authorized to it. The Power of Attorney of the Encumbrance Rights (SKMHT) must be made in two forms namely the notarial deed or the deed of the land deed official (PPAT) as stipulated by the provisions of Article 15 paragraph (1) of the Law Number 4 of 1996 on the Encumbrance Rights of the Land Along with Bodies Relating to Land. The enactment of the National Land Agency Regulation Number 8 of 2012 requires that the SKMHT shall be made ??in accordance with the format of the attachment of the Regulation. . While the SKMHT in the form of notarial deed shall be made ??in accordance with the provisions of Article 1868 of the Civil Code, the Article 38 of the Revised Law on the Position of the Land Deed Official (UUJNP), and the Article 15 of the Law on The Encumbrance Rights (UUHT). This results in the different arrangements resulting in the lack of uniformity of the SKMHT forms made ??by a notary or the land deed official (PPAT) which giving rise to the legal uncertainty of the form of the SKMHT and the legal effect of the SKMHT made in the form of a notarial deed. The study is a normative legal research, intended to examine the differences in the SKMHT arrangement between the provisions of Article 15 paragraph (1) of The Encumbrance Rights (UUHT) with the Regulation of the Head of National Land Agency (Perkaban) Number 8 of 2012. The study uses the statutory approach that is supported by the literature, legal theory, the opinions of the scholars, as well as the legal dictionaries, as its legal materials. The findings of the study show that the Regulation of the Head of National Land Agency (Perkaban) Number 8 of 2012 does not abolish the SKMHT  in the form of a notarial deed as provided in Article 15 paragraph (1) of The Encumbrance Rights (UUHT). the SKMHT in the form of a notarial deed shall be made ??in accordance with the provisions of Article 1868 of the Civil Code, the Article 38 of the Revised Law on the Position of the Land Deed Official (UUJNP), and the Article 15 of the Law on The Encumbrance Rights (UUHT), while the SKMHT in the form of the land deed official (PPAT) shall be made in accordance with the provisions of the Regulation of the Head of National Land Agency (Perkaban) Number 8 of 2012 along with its attachments. It is expected that the firm provisions which regulate the SKMHT in the forms of the notarial deed should be enacted in order to create its legal certainty.
Keywords: The Power of Attorney of the Encumbrance Rights, the Notarial Deed, the deed of the land deed official (PPAT), the Regulation of the Head of National Land Agency (Perkaban) Number 8 of 2012.